2015
DOI: 10.1002/fes3.63
|View full text |Cite
|
Sign up to set email alerts
|

Sweet sorghum ideotypes: genetic improvement of the biofuel syndrome

Abstract: Compared to other potential feedstocks such as sugarcane, sugar beet, maize, and watermelon, sweet sorghum possesses higher levels of directly fermentable reducing sugars within the culm and the ability to accumulate high biomass under low-input production systems. In addition, it is tolerant to drought and has more efficient utilization of solar radiation and nitrogen-based fertilizers than maize and sugar cane on marginal lands that are not optimal for food production. These collectively make sweet sorghum t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 132 publications
0
33
0
3
Order By: Relevance
“…It the case of species Sorghum, the plants harvested after the growing season had lower average cellulose percentage, which amounted to 39.8%. The research of cellulose content in the range of energy application of Sorghum was performed by Anami et al (2015). The results they received were significantly lower and amounted to 23%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It the case of species Sorghum, the plants harvested after the growing season had lower average cellulose percentage, which amounted to 39.8%. The research of cellulose content in the range of energy application of Sorghum was performed by Anami et al (2015). The results they received were significantly lower and amounted to 23%.…”
Section: Resultsmentioning
confidence: 99%
“…Anami et al (2015) have investigated the content of cellulose in a variety of Sorghum for energy purposes. The authors have shown that percentage of that component is relatively low taking into account plant biomass and is 23%.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to common grain sorghum, sweet sorghum is widely found in many geographical regions, with various landraces, and is considered to be an ideal biofuel crop for first-and second-generation bioethanol production. Sorghum can produce high biomass on marginal lands that are not suitable for food or feed production (Anami et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Los sorgos dulces pueden producir entre 58 300 a 80 500 kg/ha de biomasa (Sylvester et al, 2015), en tanto que Pothisoong y Jaisil (2011) reportaron producciones entre 48 300 y 50 800 kg/ha. Potranca x Keller produjo en promedio 52 125 kg/ha de PTP, resultado que se encuentra entre el nivel inferior reportado por los primeros autores y el superior indicado por los segundos.…”
Section: Peso Total De Planta (Ptp) Peso De Tallo (Pt) Y Peso De Espunclassified
“…En los sorgos dulces las plantas más altas parecen ser la llave para obtener una mayor producción de biomasa y azúcar. Los sorgos dulces S. bicolor, frecuentemente presentan alturas de planta superiores a 3 m (Sylvester et al, 2015) (Cuadro 4). Esto depende de las condiciones de clima, suelo, manejo del cultivo, genotipo, etc.…”
Section: Días a Floración (Df) Y Altura De Planta (Ap)unclassified